Determinants of Firm‐Level Lobbying and Government Responsiveness in Agricultural Biotechnology in China. Issue 2 (3rd December 2019) - Deng, Haiyan; Hu, Ruifa; Pray, Carl; Jin, Yanhong; Li, Zhonghua
Abstract: Understanding what stimulates agribusiness firms to lobby the government and what makes the government responsive to lobbying are the two issues that have been discussed extensively in the debates concerning determinants of biotechnology policy. This paper examines the factors influencing agribusiness firms' lobbying and government response using econometric modeling on a new data set of 160 leading agribusiness firms in the food, feed, chemical, and seed industries in China. The results show that approximately 10% of agribusiness firms lobbied the government about biotechnology policy and regulations and over half of those that lobbied received a verbal or written acknowledgment from government agencies. Seed and feed companies are more likely to engage in lobbying than chemical companies. Owning GM patents not only has a positive impact on firms' lobbying activities, but firms with these patents are more likely to receive a government response to their lobbying efforts. The experience of selling GM products does not significantly influence lobbying activities or response from the government. Abstract : 中国农业生物技术中公司游说和政府响应的决定因素: 有关生物技术政策决定因素的学术辩论一直在大量探讨两个问题，即是什么在激励农业综合企业游说政府，又是什么让政府响应游说。本文通过对一项有关中国食品、饲料、化工和种子产业中160家领先农业综合公司的新数据集进行计量经济模型研究，检验了影响农业综合企业游说和政府响应的影响因素。研究结果显示，几乎近百分之十的农业综合企业针对生物技术政策和监管向政府进行游说，而这部分公司中超过一半收到了政府机构的口头回复或书面回复。比起化工企业，种子和饲料企业更有可能参与游说。拥有转基因专利不仅对企业游说活动具有积极影响，同时这些公司还更可能因其游说行动而收到政府回应。拥有销售转基因产品的经历并不会对游说活动或政府响应产生显著影响。 Abstract : Determinantes del cabildeo a nivel empresarial y la capacidad de respuesta del gobierno en biotecnología agrícola en China: Comprender qué es lo que estimula a las empresas de agronegocios para presionar al gobierno y lo que hace que el gobierno responda al cabildeo son dos temas que se han discutido ampliamente en los debates sobre los determinantes de la política de biotecnología. Este documento examina los factores que influyen en el cabildeo de las empresas de agronegocios y la respuesta del gobierno utilizando modelos econométricos en un nuevo conjunto de datos de 160 empresas agroindustriales líderes en las industrias de alimentos, piensos, químicos y semillas en China. Los resultados muestran que aproximadamente el 10% de las empresas de agronegocios cabildearon al gobierno sobre políticas y regulaciones de biotecnología y más de la mitad de las que presionaron recibieron un reconocimiento verbal o escrito de las agencias gubernamentales. Las empresas de semillas y piensos tienen más probabilidades de participar en el cabildeo que las empresas químicas. Ser propietario de patentes de GM no solo tiene un impacto positivo en las actividades de cabildeo de las empresas, sino que las empresas con estas patentes tienen más probabilidades de recibir una respuesta del gobierno a sus esfuerzos de cabildeo. La experiencia en la venta de productos GM no influye significativamente en las actividades de cabildeo o en la respuesta del gobierno.